Strategies for Developing Teachers' Digital Teaching Competency in Fujian Higher Vocational Colleges - Mao, Chen; Noirid, Surachet (Journal of Ecohumanism, 2025)
This study outlines a strategy for developing digital teaching skills among faculty at Fujian's vocational colleges. It has three goals: to identify key components of digital teaching competency, to evaluate current and desired levels of competency, and to create effective strategies for improvement. The research involves 412 educators and uses interviews, questionnaires, and evaluations.The strategy includes four components with 14 indicators: Digital Awareness, Skills and Training, Institutional Construction, and Teaching Experience. Current competency is moderate, with Teaching Experience highest. Desired levels are higher, led by Digital Skills. Priorities are to establish support systems, enhance skills, foster positive attitudes, and accumulate experience.Experts rate the strategy highly for appropriateness, accuracy, and feasibility. It meets the colleges' needs, covers all aspects of management and teaching, and provides a model for other institutions to follow in promoting digital teaching and cultural heritage.